The New Alchemy: Economic liberalism, neoliberalism, and Thomas Pynchon's Against the Day1. Issue 3 (16th March 2019) - Carswell, Sean
ABSTRACT: This article utilises Karl Polanyi's landmark 1944 text The Great Transformation to explicate economic liberalism as it is represented in Thomas Pynchon's Against the Day . Polanyi argues that a fundamental flaw of economic liberalism is its treatment of labour and land as commodities. This commodification leads to economic and ecological disasters. Pynchon demonstrates these disasters throughout his encyclopaedic novel. Further, using Pynchon's metaphor of bilocation – literally being in two places at the same time – this article 'bilocates' the economic liberalism represented in the novel with contemporary neoliberalism, specifically as neoliberalism is characterised by David Harvey and Wendy Brown. Ultimately, this exploration leads to a discussion of freedom within a neoliberal society, particularly as it is envisioned in Pynchon's novel.